Утилизация бросового тепла газопоршневых установок на базе низкокипящих рабочих тел - Чемерис, И.Ф.; Оксень, Ю. И.; Радюк, М. В. (My University, 2008)
Розроблено теплову схему утилізації тепла, яке виробляється газопоршневими установками. Досліджено використання різних робочих тіл з температурою перегріву, яка наближається до температури їх термічної стійкості. Досліджено вплив величини теплової потужності на виробку електроенергії і ККД установки.

The thermal scheme of heat utilization producing by internal combustion engines is worked out. The different working fluids with superheat temperatures which are close to their thermal stability temperatures are used. The influence of thermal power input on electricity generation and efficiency output is investigated.
Utilization of waste heat from cogeneration facilities on the basis of low-boiling working fluids
Keywords: Когенерация; утилизация бросового тепла; газопоршневая установка; низкопотенциальный источник тепла; высокопотенциальный источник тепла; высокотемпературный теплообменник; низкотемпературный теплообменник; конденсатор; насос; турбина; электрический генератор